Potencial eólico offshore no Brasil: localização de áreas nobres através de análise multicritério - Silva, Amanda Jorge Vinhoza de Carvalho (2019)
In this study, the Offshore Wind Energy Potential is assessed for Brazil, with the purpose of mapping the most suitable areas for the source’s development and of estimating the capacity that could be installed in Brazilian waters. The analysis was performed under diverse perspectives: Theoretical, Technical, Environmental, Social and Economic, through the imposition of limitations between levels. Given that, data were acquired from the Electric Energy Research Center (CEPEL) containing the annual mean offshore wind speeds off the coast of Brazil, measured at a 100 meters height. They were mapped with the ArcMAp software and then overlaid with the exclusions at each potential level. The final selection of Preferential Areas was based on a MultiCriteria Spatial Analysis that considers comparative economic factors. Results indicate the Brazilian Offshore Wind Gross Potential is 1,687.6 GW; the Technical Potential is 1,064.2 GW; and the Environmental and Social Potential, the most restricted one, is 330.5 GW, what represents the double of the total capacity currently installed in the country and more than 20 times the onshore wind capacity. The 10 Preferential Areas, resulting from the economic analysis, total 126 GW of capacity and are located in the Northeast region, between the states of Pará and Rio Grande do Norte, and in the South region, in Santa Catarina and Rio Grande do Sul. Thus, this work concludes that, regarding offshore wind energy in Brazil, it is possible to combine technical viability, installation costs minimization and environmental and social impacts prevention, with a great wind resource.